Association between serum lipid profile and erectile dysfunction in adult patients with type 2 diabetes mellitus - Siddique, M. Tanvir A. (International Journal of Research in Dermatology, 2026)
Background: Diabetes mellitus (DM) is a major global health concern, with men affected having a threefold higher risk of erectile dysfunction (ED) than non-diabetic men. The study aims to determine the association between serum lipid profile abnormalities and ED in adult patients with type 2 diabetes mellitus (T2DM). Methods: This cross-sectional study at the Departments of Dermatology and Venereology and Endocrinology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh (March 2019–July 2020) included 382 married men with T2DM. Age, body mass index (BMI), diabetes duration, glycated haemoglobin (HbA1c), and lipid profile were recorded. ED was assessed using the Bengali IIEF-5 and classified as severe, moderate, mild, or no ED. Data were analyzed with statistical package for the social sciences (SPSS) v23.0 (t-test, Chi-square; p≤0.05). Results: Among 382 men with type 2 diabetes, 158 (41.4%) had ED. Those with ED were older (48.7 versus 44.3 years), had higher BMI (26.5 versus 25.9 kg/m²), higher HbA1c (8.21 versus 7.95), and longer diabetes duration (7.14 versus 5.95 years; all p ≤ 0.05). ED severity was severe 10.2%, moderate 13.4%, and mild 17.8%. Triglycerides were higher (225.1 versus 200.8 mg/dl, p<0.001) and LDL-C slightly lower (131.97 versus 136.02 mg/dl, p=0.025), with no differences in total cholesterol or HDL-C. Conclusion: Elevated triglycerides and slightly lower LDL-C are associated with erectile dysfunction in men with T2DM, highlighting the role of lipid abnormalities in its development.